An efficient synthesis of styrenyl enamides from 4-aryl-2-oxazolidinones in the presence of strong base. Issue 41 (7th October 2015) - Zou, Kaihe; Ye, Jinxing; Wu, Xin-Yan
Graphical abstract: Abstract: Efficient synthesis of styrenyl enamides can be achieved from the corresponding 4-aryl-2-oxazolidinones, 2-thioxooxazolidines, and 2-thioxothiazolidines in the presence of the strong base lithium diisopropylamine. The reaction proceeded efficiently to achieve the enamides in good to excellent yields (up to 92%). This reaction provides an easy, rapid, and good-yielding method for the synthesis of styrenyl enamides.